Al-Ijarah dalam Perspektif Hadis; Kajian Hadis dengan Metode Maudhu’iy - Husain Insawan (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
The purpose of this study was to discover the conception of al-Ijarah in the perspective ofthe hadith; and to know the quality of a hadith which discusses al-Ijarah by first doing naqdal-sanad, naqd al-mart, i'tibar hadith about trustworthiness and his muttabi'an, andgiving syarh (explanation) intact about a representative hadith, so it can serve as a legalumbrella associated with al-Ijarah activities.Using Takhrij al-Hadith bi al-Fazh and Takhrij al-Hadis bi al-Maudhu'iy, this studytraces a number of hadiths and compiles them into a theme; then one of the reperesentativehadiths of the many hadiths that deal with al-Ijarah will be examined more broadly anddeeply.The translations of hadith that are deemed representative are: "Having said Abdullah, AbuIshaq Ibn 'Isa said to me (Ahmad Ibn Hanbal): indeed Malik, from al-Zuhriy, from IbnMuhayyashah, from his father (Sa'ad Ibn Muhayyashah); asked the permission of theMessenger of Allah to forbid the hunting, (Rasulullah) forbade the hiring, so he(Muhayyashah) did not ask again about it, until the Messenger of Allah said to him: "Feedyour gardener and feed your brother”.After a search of the hadith narrated by Ahmad Ibn Hanbal (164-241 H) it is known thatthe hadith is classical ahadith ahad masyhur and qualified sahih based on the assessment ofexperts hadith that assess its sanad continued up to the Messenger of Allah. and thenarrators of these traditions are fair, sabt (tsiqah), morals commendable, shaduq, ashahasanid, and a'lam al-nas. Thus, the hadith narrated by Ahmad Ibn Hanbal can be used as alegal umbrella on the activities of al-Ijarah by looking at the context in contemporary life.